Copolymer and preparation method thereof, polylactic acid fiber and preparation method thereof, copolymer fiber composition, fracturing fluid and application

By using a fracturing fluid system that combines copolymers with salt-resistant and high-temperature-resistant functional groups and rigid structures with polylactic acid fibers, it is difficult for fracturing fluid in deep well high-temperature reservoirs to be both high-temperature, easy to carry sand and low friction resistance. , easy reflux and low damage performance problems have achieved efficient fracturing transformation under 158℃ and meet the requirements of green and sustainable development.

CN119431658AActive Publication Date: 2025-02-14PETROCHINA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310967300.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

It is difficult for the prior art to use fracturing fluid in deep well high temperature reservoirs to have high temperature resistance, easy sand carrying, low friction resistance, easy reflux and low damage properties.

Method used

A copolymer is used that contains specific structural units, has salt-resistant and high-temperature-resistant functional groups and a rigid structure, and is combined with polylactic fibers to form a fracturing liquid system.

Benefits of technology

The fracturing fluid system exhibits excellent high temperature resistance, sand carrying performance and low friction resistance characteristics under deep well conditions with a maximum temperature of 158°C. The reflux fluid is recyclable, complies with the green and sustainable development strategy, and is cheap in production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431658A_ABST
    Figure CN119431658A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas reservoir exploitation, and discloses a copolymer and a preparation method thereof, a polylactic acid fiber and a preparation method thereof, a copolymer fiber composition, a fracturing fluid and application. The copolymer comprises a structural unit A as shown in a formula 1, a structural unit B as shown in a formula 2, a structural unit C as shown in a formula 3 and / or a formula 4 and a structural unit D as shown in a formula 5 and / or a formula 6, and the content of the structural unit A is 40-60 wt%, the content of the structural unit B is 20-30 wt%, the content of the structural unit C is 15-20 wt%, and the content of the structural unit D is 5-25 wt% on the basis of the total weight of the copolymer. The copolymer has excellent salt resistance, high temperature resistance and stability. A fracturing fluid system containing the copolymer can be applied to a high-temperature deep well with the highest temperature of 158 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas reservoir exploitation, and in particular to a copolymer and a preparation method thereof, polylactic acid fiber and a preparation method thereof, a copolymer fiber composition and a fracturing fluid and applications thereof. Background Art

[0002] The demand for oil and natural gas energy in countries around the world is rapidly increasing. People are shifting their focus from conventional reservoirs to the exploration and development of deep well high-temperature reservoirs. However, due to the increasingly complex geological conditions of reservoirs, the difficulty of reservoir transformation is also increasing. Fracturing is one of the important technical measures for reservoir production increase and transformation, and fracturing fluid is an important part of the fracturing process. Selecting a suitable fracturing fluid with good performance is the key technical point to achieve reservoir fracturing transformation.

[0003] At present, the fracturing fluids commonly used at home and abroad are divided into two categories: natural plant guar fracturing fluids and artificial synthetic polymer fracturing fluid systems. Guar fracturing fluids have high viscosity and excellent sand carrying performance, but they have large pipeline friction and high residue content, which causes great damage to the reservoir. Increasing the amount of guar gum to improve the temperature resistance of the fracturing fluid will greatly increase the material cost. The slick water system in the polymer fracturing fluid can create large-scale complex network seams and connect natural fractures in the formation. It is the main fracturing fluid for volume fracturing of unconventional oil and gas reservoirs. However, the conventional slick water system is not resistant to high temperatures, has poor sand carrying performance, and cannot carry the proppant to the fracture to form an effective fracture channel. CN108841370A adopts the reverse microemulsion method to prepare the polymer thickener, and introduces polyvinyl acetal high-strength fiber to increase the sand-carrying performance of the fracturing fluid, which can be used for medium and low temperature (below 70 degrees) reservoir fracturing transformation, but there is still the problem of poor temperature resistance of the slick water fracturing fluid, and the construction site needs to be equipped with designated equipment for dissolving and dispersing the fiber, and the fiber dispersion performance is poor, which seriously reduces the efficiency of the fiber fracturing fluid. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the existing deep well high temperature reservoir fracturing fluid is difficult to have high temperature resistance, easy sand carrying, low friction, easy flowback and low damage performance, and provide a copolymer and a preparation method thereof, polylactic acid fiber and a preparation method thereof, a copolymer fiber composition and a fracturing fluid and application thereof, the copolymer has a salt-resistant and high temperature resistant functional group and a rigid structure, and the fracturing fluid system containing the copolymer has the excellent characteristics of easy sand carrying, high sand carrying, low friction, easy flowback and low damage on the basis of salt resistance and high temperature resistance. In addition, the fracturing fluid flowback fluid is recyclable, which conforms to the green sustainable development strategy and has low production cost.

[0005] In order to achieve the above object, the first aspect of the present invention provides a copolymer, wherein the copolymer contains a structural unit A shown in Formula 1, a structural unit B shown in Formula 2, a structural unit C shown in Formula 3 and / or Formula 4, and a structural unit D shown in Formula 5 and / or Formula 6,

[0006]

[0007] Wherein, in Formula 1, R1 is hydrogen or methyl;

[0008] In formula 2, R2 is hydrogen or methyl;

[0009] In formula 3, R3 is hydrogen or methyl; R4 is Wherein, R5 and R5' are each independently hydrogen, methyl or Where R 12 is a C2-C6 straight chain or branched chain alkylene;

[0010] In formula 4, R6 is hydrogen or methyl; R7 is methyl, benzyl or Where R 13 is methylene, C2-C6 straight chain or branched alkylene; n is an integer of 1-4;

[0011] In Formula 5, R8 is hydrogen or methyl; R9 is Among them, R 14 C 10 -C 20 A straight chain or branched alkyl group;

[0012] In formula 6, R 10 is hydrogen or methyl, R 11 for

[0013] Wherein, based on the total weight of the copolymer, the content of the structural unit A is 40-60wt%, the content of the structural unit B is 20-30wt%, the content of the structural unit C is 15-20wt%, and the content of the structural unit D is 5-25wt%.

[0014] A second aspect of the present invention provides a method for preparing a copolymer, wherein the preparation method comprises:

[0015] (1) first mixing monomer 1, monomer 2, monomer 3 and water to obtain an aqueous solution; wherein the monomer 1 has a structure shown in formula I, the monomer 2 has a structure shown in formula II, and the monomer 3 has a structure shown in formula III and / or formula IV;

[0016] (2) in the presence of a first solvent, performing a second mixing of monomer 4 and an emulsifier to obtain an oil phase solution; wherein the monomer 4 has a structure represented by formula V and / or formula VI;

[0017] (3) in the presence of a protective atmosphere and an initiator, the aqueous phase solution and the oil phase solution are subjected to a third mixing and polymerization to obtain the copolymer;

[0018]

[0019] Wherein, in formula I, R1 is hydrogen or methyl;

[0020] In formula II, R2 is hydrogen or methyl;

[0021] In formula III, R3 is hydrogen or methyl; R4 is Wherein, R5 and R5' are each independently hydrogen, methyl or Where R 12 is a C2-C6 straight chain or branched chain alkylene;

[0022] In formula IV, R6 is hydrogen or methyl; R7 is methyl, benzyl or Where R 13 is methylene, C2-C6 straight chain or branched alkylene; n is an integer of 1-4;

[0023] In formula V, R8 is hydrogen or methyl; R9 is Among them, R 14 C 10 -C 20 A straight chain or branched alkyl group;

[0024] In Formula VI, R 10 is hydrogen or methyl, R 11 for

[0025] Wherein, based on the total mass of monomer 1, monomer 2, monomer 3 and monomer 4, the content of monomer 1 is 40-60wt%, the content of monomer 2 is 20-30wt%, the content of monomer 3 is 15-20wt%, and the content of monomer 4 is 5-25wt%.

[0026] The third aspect of the present invention provides a copolymer prepared by the above preparation method.

[0027] A fourth aspect of the present invention provides a polylactic acid fiber, wherein the polylactic acid fiber comprises polylactic acid nanospheres and polylactic acid micron fibers;

[0028] Wherein, the weight ratio of the polylactic acid nanospheres to the polylactic acid microfibers is 1:0.3-3;

[0029] Wherein, the average particle size of the polylactic acid nanospheres is 122-143nm;

[0030] Wherein, the average length of the polylactic acid micron fiber is 700-800 μm, and the average diameter is 600-800 nm.

[0031] A fifth aspect of the present invention provides a method for preparing the above-mentioned polylactic acid fiber, wherein the method for preparing the polylactic acid nanospheres comprises:

[0032] (1) dissolving polylactic acid in an organic solvent 1 under ultrasonic conditions to obtain an organic phase 1;

[0033] (2) adding the organic phase 1 of step (1) into water and mixing to obtain the polylactic acid nanospheres;

[0034] The ultrasonic conditions in step (1) include: ultrasonic time of 10-30 min, ultrasonic power of 500-900 W, and temperature of 20-30° C.

[0035] The sixth aspect of the present invention provides a copolymer fiber composition, wherein the copolymer fiber composition comprises the above copolymer, the above polylactic acid fiber or the polylactic acid fiber prepared by the above preparation method, a surfactant and an inhibitor;

[0036] Wherein, the copolymer fiber composition comprises:

[0037] 85-95 parts by weight of the copolymer;

[0038] 0.5-1.5 parts by weight of the polylactic acid fiber;

[0039] 5-10 parts by weight of the surfactant;

[0040] The polymerization inhibitor is 0.05-0.1 parts by weight.

[0041] A seventh aspect of the present invention provides a fracturing fluid, wherein the fracturing fluid comprises the above copolymer fiber composition, a breaker and water;

[0042] Wherein, the fracturing fluid comprises:

[0043] 0.5-1.5 parts by weight of the copolymer fiber composition;

[0044] The debonding agent is 0.1-0.5 parts by weight.

[0045] An eighth aspect of the present invention provides a use of the above-mentioned fracturing fluid in reservoir exploration and development.

[0046] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0047] (1) The copolymer prepared by the present invention has salt-resistant and high-temperature-resistant functional groups and a rigid structure, so that the copolymer has excellent salt resistance, high-temperature resistance and stability.

[0048] (2) The polylactic acid fiber provided by the present invention adopts polylactic acid nanospheres and polylactic acid micron fibers in a specific weight ratio. When applied to a fracturing fluid system, the sand carrying performance of the solution and the uniform dispersion of the solute can be ensured.

[0049] (3) The fracturing fluid provided by the present invention is easy to flow back, which can reduce the damage of the fracturing fluid to the reservoir, and can quickly dissolve and thicken without the need for pre-mixing of the fluid. It meets the technical requirements of large-volume and large-scale fracturing construction and can be applied to high-temperature deep wells with a maximum temperature of 158°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a graph showing the temperature and shear resistance of the fracturing fluid in Application Example 1. DETAILED DESCRIPTION

[0051] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0052] The first aspect of the present invention provides a copolymer, wherein the copolymer contains a structural unit A represented by formula 1, a structural unit B represented by formula 2, a structural unit C represented by formula 3 and / or formula 4, and a structural unit D represented by formula 5 and / or formula 6.

[0053]

[0054] Wherein, in Formula 1, R1 is hydrogen or methyl;

[0055] In formula 2, R2 is hydrogen or methyl;

[0056] In formula 3, R3 is hydrogen or methyl; R4 is Wherein, R5 and R5' are each independently hydrogen, methyl or Where R 12 is a C2-C6 straight chain or branched chain alkylene;

[0057] In formula 4, R6 is hydrogen or methyl; R7 is methyl, benzyl or Where R 13 is methylene, C2-C6 straight chain or branched alkylene; n is an integer of 1-4;

[0058] In Formula 5, R8 is hydrogen or methyl; R9 is Among them, R 14 C 10 -C 20A straight chain or branched alkyl group;

[0059] In formula 6, R 10 is hydrogen or methyl, R 11 for

[0060] Wherein, based on the total weight of the copolymer, the content of the structural unit A is 40-60wt%, the content of the structural unit B is 20-30wt%, the content of the structural unit C is 15-20wt%, and the content of the structural unit D is 5-25wt%.

[0061] The content of each structural unit in the copolymer provided by the present invention can be obtained by nuclear magnetic resonance, infrared and other detection methods, or determined by the monomers and the monomer feed amount during preparation.

[0062] In the present invention, structural unit A and structural unit B are water-soluble and can improve the solubility and thickening properties of the copolymer. Structural unit C having salt-resistant and high-temperature-resistant functional groups provides the copolymer with salt-resistant and high-temperature-resistant properties. Structural unit D having a rigid structure brings structural stability to the copolymer. The specific contents of structural unit A, structural unit B, structural unit C and structural unit D enable the copolymer to have both salt-resistant and high-temperature-resistant properties and structural stability.

[0063] Further, according to the present invention, based on the total weight of the copolymer, the content of structural unit A is 45-55wt%, the content of structural unit B is 20-25wt%, the content of structural unit C is 15-18wt%, and the content of structural unit D is 5-17wt%.

[0064] In the present invention, the contents of the structural unit A, the structural unit B, the structural unit C and the structural unit D in the copolymer are within the above ranges, and the copolymer has better salt resistance and high temperature resistance and structural stability.

[0065] According to the present invention, in Formula 1, R1 is hydrogen.

[0066] According to the present invention, in Formula 2, R2 is hydrogen.

[0067] According to the present invention, in Formula 3, R3 is hydrogen; R4 is R5 and R5' are each independently methyl or Where R 12 It is a C2-C4 straight chain or branched chain alkylene group.

[0068] Further, according to the present invention, R5 and R5' are methyl, or R5 is methyl and R5' is Where R 12 for

[0069] According to the present invention, in Formula 4, R6 is hydrogen or methyl; R7 is methyl or benzyl, and n is 2 or 3.

[0070] Further, according to the present invention, R6 is a methyl group, R7 is a methyl group, and n is 2 or 3.

[0071] According to the present invention, in Formula 5, R8 is hydrogen; R9 is Among them, R 14 C 15 -C 20 A straight chain or branched chain alkyl group.

[0072] Further, according to the present invention, R 14 for

[0073] According to the present invention, in Formula 6, R 10 is hydrogen, R 11 for

[0074] In a specific embodiment of the present invention, preferably, the copolymer is selected from one of the following copolymer combinations:

[0075] Copolymer-1: The structural unit A is derived from acrylamide (the structural formula is shown in Formula 1, R1 is hydrogen), the structural unit B is derived from acrylic acid (the structural formula is shown in Formula 2, R2 is hydrogen), and the structural unit C is derived from N,N-dimethylacrylamide (the structural formula is shown in Formula 3, R3 is hydrogen, R4 is R5 and R5' are methyl groups), the structural unit D is derived from octadecyl dimethyl propylene ammonium chloride (the structural formula is shown in Formula 5, R8 is hydrogen, R9 is Among them, R 14 for );

[0076] Copolymer-2: The structural unit A is derived from acrylamide (the structural formula is shown in Formula 1, R 1 The structural unit B is derived from acrylic acid (the structural formula is shown in Formula 2, R2 is hydrogen), the structural unit C is derived from methacryloyloxyethyl trimethylammonium chloride (the structural formula is shown in Formula 4, R6 is methyl, R7 is methyl, and n is 2), and the structural unit D is derived from sodium 4-acrylamide benzene sulfonate (the structural formula is shown in Formula 6, R 10 is hydrogen, R 11 for );

[0077] Copolymer-3: The structural unit A is derived from acrylamide (the structural formula is shown in Formula 1, R1 is hydrogen), the structural unit B is derived from acrylic acid (the structural formula is shown in Formula 2, R2 is hydrogen), and the structural unit C is derived from 2-acrylamide-2-methylpropanesulfonic acid (the structural formula is shown in Formula 3, R3 is hydrogen, R4 is R5 is methyl, R5' is Where R 12 for ), the structural unit D is derived from octadecyl dimethyl propylene ammonium chloride (the structural formula is shown in Formula 5, R8 is hydrogen, R9 is Among them, R 14 for ).

[0078] According to the present invention, the weight average molecular weight of the copolymer is 8 million g / mol-10 million g / mol, preferably 8.5 million g / mol-9 million g / mol.

[0079] A second aspect of the present invention provides a method for preparing a copolymer, wherein the preparation method comprises:

[0080] (1) first mixing monomer 1, monomer 2, monomer 3 and water to obtain an aqueous solution; wherein the monomer 1 has a structure shown in formula I, the monomer 2 has a structure shown in formula II, and the monomer 3 has a structure shown in formula III and / or formula IV;

[0081] (2) in the presence of a first solvent, performing a second mixing of monomer 4 and an emulsifier to obtain an oil phase solution; wherein the monomer 4 has a structure represented by formula V and / or formula VI;

[0082] (3) in the presence of a protective atmosphere and an initiator, the aqueous phase solution and the oil phase solution are subjected to a third mixing and polymerization to obtain the copolymer;

[0083]

[0084]

[0085] Wherein, in formula I, R1 is hydrogen or methyl;

[0086] In formula II, R2 is hydrogen or methyl;

[0087] In formula III, R3 is hydrogen or methyl; R4 is Wherein, R5 and R5' are each independently hydrogen, methyl or Where R 12 is a C2-C6 straight chain or branched chain alkylene;

[0088] In formula IV, R6 is hydrogen or methyl; R7 is methyl, benzyl or Where R 13 is methylene, C2-C6 straight chain or branched alkylene; n is an integer of 1-4;

[0089] In formula V, R8 is hydrogen or methyl; R9 is Among them, R 14 C 10 -C 20 A straight chain or branched alkyl group;

[0090] In Formula VI, R 10 is hydrogen or methyl, R 11 for

[0091] Wherein, based on the total mass of monomer 1, monomer 2, monomer 3 and monomer 4, the content of monomer 1 is 40-60wt%, the content of monomer 2 is 20-30wt%, the content of monomer 3 is 15-20wt%, and the content of monomer 4 is 5-25wt%.

[0092] Further, according to the present invention, based on the total mass of monomer 1, monomer 2, monomer 3 and monomer 4, the content of monomer 1 is 45-55wt%, the content of monomer 2 is 20-25wt%, the content of monomer 3 is 15-18wt%, and the content of monomer 4 is 5-17wt%.

[0093] According to the present invention, in formula I, R1 is hydrogen.

[0094] According to the present invention, in formula II, R2 is hydrogen.

[0095] According to the present invention, in formula III, R3 is hydrogen; R4 is R5 and R5' are methyl, or R5 is methyl and R5' is Where R 12 for

[0096] According to the present invention, in formula IV, R6 is hydrogen or methyl; R7 is methyl or benzyl, and n is 2 or 3.

[0097] According to the present invention, in formula V, R8 is hydrogen; R9 is Among them, R 14 C 15 -C 20 A straight chain or branched chain alkyl group.

[0098] According to the present invention, in formula VI, R 10 is hydrogen, R 11 for

[0099] In a specific embodiment of the present invention, the monomer 1 is acrylamide (the structural formula is shown in Formula I, and R1 is hydrogen).

[0100] In a specific embodiment of the present invention, the monomer 2 is acrylic acid (the structural formula is shown in Formula II, and R2 is hydrogen).

[0101] In one embodiment of the present invention, the monomer 3 is selected from N,N-dimethylacrylamide (the structural formula is shown in Formula III, R3 is hydrogen, R4 is R5 and R5' are methyl), 2-acrylamide-2-methylpropanesulfonic acid (the structural formula is shown in Formula III, R3 is hydrogen, R4 is R5 is methyl, R5' is Where R 12 for ), N-vinyl pyrrolidone (the structural formula is shown in Formula III, R3 is hydrogen, R4 is ), methacryloyloxyethyl trimethylammonium chloride (the structural formula is shown in Formula IV, R6 is methyl, R7 is methyl, and n is 2), methacryloyloxypropyl trimethylammonium chloride (the structural formula is shown in Formula IV, R6 is methyl, R7 is methyl, and n is 3), acryloyloxyethyl trimethylammonium chloride (the structural formula is shown in Formula IV, R6 is hydrogen, R7 is methyl, and n is 2), 2-(acryloyloxy)-N-benzyl-N,N-dimethylethane-1-ammonium chloride (the structural formula is shown in Formula IV, R6 is hydrogen, R7 is benzyl, and n is 2) and 2-acrylamido-2-methylpropanesulfonic acid (the structural formula is shown in Formula III, R3 is hydrogen, R4 is methyl, R5 is Where R 12 for ) at least one of.

[0102] In a specific embodiment of the present invention, the monomer 4 is selected from octadecyl dimethyl propylene ammonium chloride (the structural formula is shown in formula V, R8 is hydrogen, R9 is Among them, R 14 for ) and / or sodium 4-acrylamide benzenesulfonate (structural formula as shown in formula VI, R 10 is hydrogen, R 11 for ).

[0103] According to the present invention, the first mixing condition in step (1) includes: adjusting the pH to 6-7, the temperature to 20-30° C., and the time to 0.5-2 h.

[0104] According to the present invention, the second mixing conditions in step (2) include: a stirring rate of 1000-1500 r / min, a stirring temperature of 20-30° C., and a stirring time of 10-30 min.

[0105] According to the present invention, the third mixing condition in step (3) includes: a stirring rate of 1000-1600 r / min, a stirring temperature of 20-30° C., and a stirring time of 5-30 min.

[0106] According to the present invention, the polymerization reaction conditions in step (3) include: temperature of 36-45° C. and time of 2-3 h.

[0107] According to the present invention, the polymerization in step (3) further comprises: adding a second solvent or an initiator so that the polymerization reaction temperature is 36-45°C.

[0108] According to the present invention, the concentration of the monomer 1 in the aqueous solution is 30-40 wt %.

[0109] According to the present invention, there is no particular limitation on the concentration of the monomer 4 in the oil phase solution, as long as the monomer 4 and the emulsifier can be fully mixed.

[0110] According to the present invention, based on the total mass of monomers, emulsifiers and initiators, the contents of monomer 1, monomer 2, monomer 3 and monomer 4 are 90-98.2wt%, the content of initiator is 0.2-1.2wt%, and the content of emulsifier is 1.6-9wt%.

[0111] In the present invention, the total mass of monomers is the sum of the masses of monomer 1, monomer 2, monomer 3 and monomer 4.

[0112] In the present invention, the content of the initiator is the total mass of the initiator in step (3).

[0113] According to the present invention, the initiator is at least one of an azo initiator, a peroxide initiator and a redox initiator, preferably at least one of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, tert-butyl hydroperoxide, sodium sulfite and sodium bisulfite.

[0114] According to the present invention, the initiator is at least one of azobisisobutyronitrile, benzoyl peroxide, tert-butyl hydroperoxide-sodium bisulfite composite system and potassium persulfate-sodium sulfite composite system.

[0115] In a specific embodiment of the present invention, the weight ratio of tert-butyl hydroperoxide to sodium bisulfite is 1:0.3-0.5.

[0116] In a specific embodiment of the present invention, the weight ratio of potassium persulfate to sodium sulfite is 1:1-2.

[0117] According to the present invention, the first solvent is at least one of kerosene, diesel, white oil, cyclohexane, benzene, toluene and petroleum ether.

[0118] According to the present invention, the emulsifier is a nonionic surfactant, preferably at least one of sorbitan monostearate (Span 60), sorbitan oleate (Span 80), polyoxyethylene sorbitan monostearate (Tween 60), polysorbate 80 (Tween 80) and dodecylphenol polyoxyethylene ether (OP-10).

[0119] According to the present invention, the emulsifier is selected from one of Span 60 / Span 80 compound emulsifier, Tween 60 / Tween 80 compound emulsifier, Span 80 / OP-10 compound emulsifier or Tween 80 / OP-10 compound emulsifier.

[0120] In a specific embodiment of the present invention, the mass ratio of Span 60 to Span 80 is 1:1-2, the mass ratio of Tween 60 to Tween 80 is 1:0.6-1, the mass ratio of Span 80 to OP-10 is 1:1-2, and the mass ratio of Tween 80 to OP-10 is 1:1-2.

[0121] In the present invention, a compound emulsifier is selected to achieve better emulsification effect and more excellent dispersing performance.

[0122] According to the present invention, the second solvent is water.

[0123] The third aspect of the present invention provides a copolymer prepared by the above preparation method.

[0124] In the present invention, the copolymer prepared by the above preparation method can be applied to a reservoir fracturing fluid system, and can improve the high temperature resistance, salt resistance and shear resistance of the fracturing fluid system.

[0125] A fourth aspect of the present invention provides a polylactic acid fiber, wherein the polylactic acid fiber comprises polylactic acid nanospheres and polylactic acid micron fibers;

[0126] Wherein, the weight ratio of the polylactic acid nanospheres to the polylactic acid microfibers is 1:0.3-3;

[0127] Wherein, the average particle size of the polylactic acid nanospheres is 122-143nm;

[0128] Wherein, the average length of the polylactic acid micron fiber is 700-800 μm, and the average diameter is 600-800 nm.

[0129] In the present invention, the content of the L-isomer of the polylactic acid used as the raw material of the polylactic acid nanospheres and the polylactic acid microfibers is 90-99 wt %.

[0130] In the present invention, the polylactic acid fiber comprising polylactic acid nanospheres and polylactic acid micron fibers in a specific weight ratio is applied to a fracturing system to ensure uniform dispersion of the solution and improve sand carrying performance.

[0131] A fifth aspect of the present invention provides a method for preparing the above-mentioned polylactic acid fiber, wherein the method for preparing the polylactic acid nanospheres comprises:

[0132] (1) dissolving polylactic acid in an organic solvent 1 under ultrasonic conditions to obtain an organic phase 1;

[0133] (2) adding the organic phase 1 of step (1) into water and mixing to obtain the polylactic acid nanospheres;

[0134] The ultrasonic conditions in step (1) include: ultrasonic time of 10-30 min, ultrasonic power of 500-900 W, and temperature of 20-30° C.

[0135] In the present invention, the polylactic acid nanospheres obtained under specific ultrasonic and mixing conditions have different sizes, and the polylactic acid fibers composed of the polylactic acid nanospheres are applied to the fracturing fluid system, so that the fracturing fluid system is evenly dispersed.

[0136] According to the present invention, the mixing conditions in step (2) include: a stirring speed of 500-700 r / min and a stirring temperature of 20-30°C.

[0137] According to the present invention, the organic solvent 1 is a mixed solution of ethanol and acetone.

[0138] According to the present invention, the volume ratio of ethanol to acetone is 1:1-3.

[0139] According to the present invention, the L-isomer content of the polylactic acid fiber is 90-99wt%.

[0140] In the present invention, polylactic acid can be prepared by the following method:

[0141] (1) Under anhydrous and oxygen-free conditions, lactic acid and stannous chloride are mixed and reacted at 120-150° C. for 5-10 hours to obtain a mixture 1;

[0142] (2) dissolving the mixture in chloroform, adding it into methanol, mixing, and drying to obtain the polylactic acid.

[0143] According to the present invention, the weight ratio of stannous chloride to lactic acid is 1:3000-5000.

[0144] According to the present invention, in step (1), stannous chloride is prepared into a 0.05-0.2 wt % solution and then mixed with lactic acid, wherein the solvent of the solution is chloroform.

[0145] According to the present invention, there is no particular limitation on the amount of chloroform used, as long as the mixture 1 is fully dissolved.

[0146] According to the present invention, in step (2), the mixing conditions include: until a large amount of white fibrous matter is generated.

[0147] According to the present invention, the drying conditions include: a temperature of 80-100° C. and a drying time of 5-10 hours, until the polylactic acid reaches a constant weight.

[0148] In the present invention, the polylactic acid micron fiber can be prepared by the following method:

[0149] Pour 5-10wt% polylactic acid dichloromethane solution into a spinning tube, spin at a spinning distance of 15-20cm between the receiving screen and the spinneret, spin at a spinning flow of 0.1-0.3mL / h and a spinning voltage of 7-15KV, and dry at 20-30°C to obtain polylactic acid micron fibers.

[0150] The sixth aspect of the present invention provides a copolymer fiber composition, wherein the copolymer fiber composition comprises the above copolymer, the above polylactic acid fiber or the polylactic acid fiber prepared by the above preparation method, a surfactant and an inhibitor;

[0151] Wherein, the copolymer fiber composition comprises:

[0152] 85-95 parts by weight of the copolymer;

[0153] 0.5-1.5 parts by weight of the polylactic acid fiber;

[0154] 5-15 parts by weight of the surfactant;

[0155] The polymerization inhibitor is 0.05-0.1 parts by weight.

[0156] In the present invention, the copolymer fiber composition adopts polylactic acid nanospheres and polylactic acid micron fibers in a specific weight ratio, the polylactic acid nanospheres ensure the uniform dispersion of the solution, and the polylactic acid micron fibers improve the sand carrying performance of the solution.

[0157] According to the present invention, the surfactant is selected from at least one of nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether and dodecylphenol polyoxyethylene ether.

[0158] According to the present invention, the polymerization inhibitor is at least one of polyvinyl alcohol, sodium polyacrylate and sodium alginate.

[0159] A seventh aspect of the present invention provides a fracturing fluid, wherein the fracturing fluid comprises the above copolymer fiber composition, a breaker and water;

[0160] Wherein, the fracturing fluid comprises:

[0161] 0.5-1.5 parts by weight of the copolymer fiber composition;

[0162] The debonding agent is 0.1-0.5 parts by weight.

[0163] According to the present invention, the breaker is at least one of potassium persulfate, sodium persulfate and ammonium persulfate.

[0164] In the present invention, compared with the fracturing fluid system composed of the copolymer and polyvinyl acetal high-strength fiber not described in the present invention, the fracturing fluid prepared by the present invention can be applied to deep wells with a maximum temperature of 158°C, and can be quickly dissolved and thickened without the need for advance liquid preparation, thereby meeting the technical requirements for large-volume and large-scale fracturing construction.

[0165] An eighth aspect of the present invention provides a use of the fracturing fluid described in the seventh aspect in reservoir exploration and development.

[0166] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited to the following description.

[0167] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.

[0168] The content of each structural unit in the copolymers prepared in the following examples and comparative examples is determined by the monomers used in the preparation and the monomer feed amount. In the present invention, the monomer feed is completely reacted during the preparation.

[0169] The weight average molecular weight of the copolymer was measured by GPC.

[0170] According to "SY / T 6376-2008 General Technical Conditions for Fracturing Fluids", the apparent viscosity of the fracturing fluid was tested. 350 mL was placed in a constant temperature water bath at 30°C for 4 hours, and the rotation speed was 100 r / min (shear rate was 170s -1 ) at the apparent viscosity.

[0171] The temperature resistance of the fracturing fluid was tested according to SY / T 5107-2005 "Method for evaluating the performance of water-based fracturing fluid". The specific conditions are as follows: After the viscometer sample cup is filled with fracturing fluid, the sample is heated. The heating rate is controlled at 3℃ / min±0.2℃ / min, and the test is started at 30℃. At the same time, the rotor is heated at a shear rate of 170s -1 The fracturing fluid is rotated and subjected to continuous shearing under heating conditions, and the temperature corresponding to the apparent viscosity dropping to 50 mPa·s is used to characterize the temperature resistance of the sample.

[0172] The surface tension of fracturing fluid was tested according to SY / T 5370-1999 “Surface and interfacial tension determination method”.

[0173] The drag reduction performance of the copolymer fiber composition was tested using an indoor pipe friction tester.

[0174] Preparation Example

[0175] Under anhydrous and oxygen-free conditions, 500g of racemic lactide was mixed with 0.05wt% stannous chloride, dehydrated under reduced pressure for 2h, the ampoule was sealed by high-temperature melting, and dehydrated and condensed at 130℃ for 5h, the polylactic acid product was collected and dissolved in chloroform, the solution was poured into methanol, and stirred until a large amount of white fibrous material was produced, and vacuum dried at 80℃ for 5h to constant weight to obtain 400g of polylactic acid. The content of the left-handed isomer of polylactic acid was 95wt%.

[0176] Preparation of copolymers

[0177] Example A-1

[0178] (1) 55 g of acrylamide (monomer 1, the structural formula is shown in formula I, R1 is hydrogen), 25 g of acrylic acid (monomer 2, the structural formula is shown in formula II, R2 is hydrogen) and 15 g of N,N-dimethylacrylamide (monomer 3, the structural formula is shown in formula III, R3 is hydrogen, R4 is R5 and R5' are methyl groups) and water were mixed at 25°C for 1 hour, and KOH was added to adjust the pH value of the solution to 6 to obtain an aqueous phase solution, wherein the concentration of acrylamide was 30 wt%.

[0179] (2) 5 g of octadecyl dimethyl propylene ammonium chloride (monomer 4, the structural formula is shown in formula V, R8 is hydrogen, R9 is Among them, R 14 for ), 5g emulsifier and white oil, stirred at 1000r / min for 10min at 25℃ until uniformly dispersed to obtain an oil phase solution. The emulsifier is a composite emulsifier system of Span 60 / Span 80, and the mass ratio of Span 60 to Span 80 is 1:2.

[0180] (3) In a nitrogen atmosphere, at 25° C. and 1000 r / min, the aqueous phase solution and the oil phase solution were mixed, 0.2 g of initiator azobisisobutyronitrile was added dropwise, and polymerization was carried out at 40° C. for 10 min to obtain copolymer A1.

[0181] Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer is 98.2 wt %, the initiator is 0.2 wt % and the emulsifier is 1.6 wt %.

[0182] The weight average molecular weight is 9×10 6 Based on the total weight of the copolymer, the content of the structural unit A is 55wt%, the content of the structural unit B is 25wt%, the content of the structural unit C is 15wt%, and the content of the structural unit D is 5wt%.

[0183] Example A-2

[0184] A copolymer was prepared according to Example A-1, except that

[0185] In step (1), monomer 3 is methacryloyloxyethyl trimethylammonium chloride (the structural formula is shown in Formula IV, R6 is methyl, R7 is methyl, and n is 2).

[0186] In step (2), monomer 4 is sodium 4-acrylamide benzenesulfonate (the structural formula is shown in formula VI, R 10 is hydrogen, R 11 for ).

[0187] Copolymer A2 was obtained.

[0188] Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer is 98.2 wt %, the initiator is 0.2 wt % and the emulsifier is 1.6 wt %.

[0189] The weight average molecular weight is 8.9×10 6 The concentration of acrylamide is 35wt%, based on the total weight of the copolymer, the content of structural unit A is 55wt%, the content of structural unit B is 25wt%, the content of structural unit C is 15wt%, and the content of structural unit D is 5wt%.

[0190] Example A-3

[0191] A copolymer was prepared according to Example A-1, except that

[0192] In step (1), 45 g acrylamide, 20 g acrylic acid, and monomer 3 are 18 g 2-acrylamide-2-methylpropanesulfonic acid (the structural formula is shown in formula III, R3 is hydrogen, R4 is R5 is methyl, R5' is Where R 12 for )

[0193] In step (2), 17 g of octadecyl dimethyl propylene ammonium chloride and 10 g of emulsifier.

[0194] In step (3), 1.1 g of initiator azobisisobutyronitrile.

[0195] The copolymer A3 was obtained. Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer was 90 wt %, the initiator was 1 wt %, and the emulsifier was 9 wt %.

[0196] The weight average molecular weight is 8.8×10 6 The concentration of acrylamide is 40wt%. Based on the total weight of the copolymer, the content of structural unit A is 45wt%, the content of structural unit B is 20wt%, the content of structural unit C is 18wt%, and the content of structural unit D is 17wt%.

[0197] Example A-4

[0198] The copolymer was prepared according to Example A-1, except that the emulsifier in step (2) was a composite emulsifier system of Tween 60 / Tween 80, and the mass ratio of Tween 60 to Tween 80 was 1:0.6.

[0199] Copolymer A4 was obtained.

[0200] Based on the total mass of the monomers, the total mass of the emulsifier and the initiator, the total amount of the monomers used was 98.2 wt %, the initiator was 0.2 wt %, and the emulsifier was 1.6 wt %.

[0201] The weight average molecular weight is 8.7×10 6 The concentration of acrylamide is 30wt%. Based on the total weight of the copolymer, the content of structural unit A is 55wt%, the content of structural unit B is 25wt%, the content of structural unit C is 15wt%, and the content of structural unit D is 5wt%.

[0202] Example A-5

[0203] The copolymer was prepared according to Example A-1, except that the emulsifier in step (2) was a composite emulsifier system of Span80 / OP-10, and the mass ratio of Span80 to OP-10 was 1:1.

[0204] Copolymer A5 was obtained.

[0205] Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer is 98.2 wt %, the initiator is 0.2 wt % and the emulsifier is 1.6 wt %.

[0206] The weight average molecular weight is 8.7×10 6The concentration of acrylamide is 30wt%, based on the total weight of the copolymer, the content of structural unit A is 55wt%, the content of structural unit B is 25wt%, the content of structural unit C is 15wt%, and the content of structural unit D is 5wt%.

[0207] Example A-6

[0208] The copolymer was prepared according to Example A-1, except that the emulsifier in step (2) was a composite emulsifier system of Tween 80 / OP-10, and the mass ratio of Tween 80 to OP-10 was 1:1.

[0209] Copolymer A6 was obtained.

[0210] Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer is 98.2 wt %, the initiator is 0.2 wt % and the emulsifier is 1.6 wt %.

[0211] The weight average molecular weight is 8.5×10 6 The concentration of acrylamide is 30wt%. Based on the total weight of the copolymer, the content of structural unit A is 55wt%, the content of structural unit B is 25wt%, the content of structural unit C is 15wt%, and the content of structural unit D is 5wt%.

[0212] Example A-7

[0213] The copolymer was prepared according to Example A-1, except that the initiator in step (3) was benzoyl peroxide.

[0214] Copolymer A7 was obtained.

[0215] Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer is 98.2 wt %, the initiator is 0.2 wt % and the emulsifier is 1.6 wt %.

[0216] The weight average molecular weight is 8.6×10 6 The concentration of acrylamide is 30wt%, based on the total weight of the copolymer, the content of structural unit A is 55wt%, the content of structural unit B is 25wt%, the content of structural unit C is 15wt%, and the content of structural unit D is 5wt%.

[0217] Example A-8

[0218] The copolymer was prepared according to Example A-1, except that in step (3), the initiator was a tert-butyl hydroperoxide-sodium bisulfite composite system, and the weight ratio of tert-butyl hydroperoxide to sodium bisulfite was 1:0.5.

[0219] Copolymer A8 was obtained.

[0220] Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer is 98.2 wt %, the initiator is 0.2 wt % and the emulsifier is 1.6 wt %.

[0221] The weight average molecular weight is 8.6×10 6 The concentration of acrylamide is 30wt%. Based on the total weight of the copolymer, the content of structural unit A is 55wt%, the content of structural unit B is 25wt%, the content of structural unit C is 15wt%, and the content of structural unit D is 5wt%.

[0222] Example A-9

[0223] The copolymer was prepared according to Example A-1, except that the initiator in step (3) was a potassium persulfate-sodium sulfite composite system, and the weight ratio of potassium persulfate to sodium sulfite was 1:2.

[0224] The copolymer A9 was obtained. Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer was 98.2 wt %, the initiator was 0.2 wt % and the emulsifier was 1.6 wt %.

[0225] The weight average molecular weight is 8.6×10 6 The concentration of acrylamide is 30wt%. Based on the total weight of the copolymer, the content of structural unit A is 55wt%, the content of structural unit B is 25wt%, the content of structural unit C is 15wt%, and the content of structural unit D is 5wt%.

[0226] Example A-10

[0227] A copolymer was prepared according to Example A-1, except that

[0228] In step (1), 40 g acrylamide, 30 g acrylic acid, and 20 g N,N-dimethylacrylamide.

[0229] 5g of octadecyl dimethyl propylene ammonium chloride in step (2).

[0230] The copolymer A10 was obtained. Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer was 98.2 wt %, the initiator was 0.2 wt %, and the emulsifier was 1.6 wt %.

[0231] The weight average molecular weight is 8.5×10 6The concentration of acrylamide is 30wt%. Based on the total weight of the copolymer, the content of structural unit A is 40wt%, the content of structural unit B is 30wt%, the content of structural unit C is 20wt%, and the content of structural unit D is 5wt%.

[0232] Comparative Example DA-1

[0233] A copolymer was prepared according to Example A-1, except that

[0234] In step (1), 33 g acrylamide, 18 g acrylic acid, and 22 g N,N-dimethylacrylamide.

[0235] In step (2), 27 g of octadecyl dimethyl propylene ammonium chloride.

[0236] The copolymer DA1 was obtained. Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer was 98.2 wt %, the initiator was 0.2 wt %, and the emulsifier was 1.6 wt %.

[0237] The weight average molecular weight is 3.3×10 5 The concentration of acrylamide is 30wt%. Based on the total weight of the copolymer, the content of structural unit A is 33wt%, the content of structural unit B is 18wt%, the content of structural unit C is 22wt%, and the content of structural unit D is 27wt%.

[0238] Comparative Example DA-2

[0239] A copolymer was prepared according to Example A-1, except that

[0240] In step (1), monomer 3 is 2-methyl-2-acrylamidopropanesulfonic acid.

[0241] In step (2), monomer 4 is N-vinyl pyrrolidone.

[0242] The copolymer DA2 was obtained. Based on the total mass of the monomer, the emulsifier and the initiator, the total mass of the monomer was 98.2 wt %, the initiator was 0.2 wt %, and the emulsifier was 1.6 wt %.

[0243] The weight average molecular weight is 3.9×10 5 The concentration of acrylamide is 30wt%. Based on the total weight of the copolymer, the content of structural unit A is 55wt%, the content of structural unit B is 25wt%, the content of structural unit C is 15wt%, and the content of structural unit D is 5wt%.

[0244] Preparation of polylactic acid fiber

[0245] Example B-1

[0246] (1) Preparation of polylactic acid nanospheres: 20 g of the polylactic acid prepared in the preparation example, 400 mL of ethanol and 600 mL of acetone were mixed, and ultrasonicated at 25° C. and 500 W for 30 min to obtain a 2 wt % polylactic acid solution, which was added to distilled water and stirred at 25° C. and 500 r / min for 10 min to obtain 17.5 g of polylactic acid nanospheres. The average particle size of the polylactic acid nanospheres was 131 nm.

[0247] (2) Preparation of polylactic acid micron fiber: 200 mL 10 wt% polylactic acid dichloromethane solution was poured into a spinning tube, the spinning distance between the receiving screen and the spinneret was 15 cm, the spinning flow rate was 0.1 mL / h and the spinning voltage was 12 KV, and the spinning was carried out and dried to obtain 19.2 g of polylactic acid micron fiber. The average length of the polylactic acid micron fiber was 743 μm and the average diameter was 758 nm.

[0248] 10 g of polylactic acid nanospheres and 10 g of polylactic acid microfibers were mixed, with the weight ratio of the polylactic acid nanospheres to the polylactic acid microfibers being 1:1, to obtain polylactic acid fibers B1.

[0249] Example B-2

[0250] Polylactic acid fibers were prepared according to Example B-1, except that 9 g of polylactic acid nanospheres and 3 g of polylactic acid microfibers were mixed, and the weight ratio of polylactic acid nanospheres to polylactic acid microfibers was 3:1, to obtain polylactic acid fibers B2.

[0251] Example B-3

[0252] Polylactic acid fibers were prepared according to Example B-1, except that 3 g of polylactic acid nanospheres and 9 g of polylactic acid microfibers were mixed, and the weight ratio of the polylactic acid nanospheres to the polylactic acid microfibers was 1:3, to obtain polylactic acid fibers B3.

[0253] Example B-4

[0254] Polylactic acid fiber was prepared according to Example B-1, except that in the preparation of (1) polylactic acid nanospheres, ultrasound was applied at 30°C and 900W for 10 min to obtain polylactic acid fiber B4.

[0255] Example B-5

[0256] Polylactic acid fiber was prepared according to Example B-1, except that in the preparation of (1) polylactic acid nanospheres, the mixture was stirred at 700 r / min at 30° C. for 30 min to obtain polylactic acid fiber B5.

[0257] Comparative Example DB-1

[0258] Polylactic acid fiber was prepared according to Example B-1, except that 3 g of polylactic acid nanospheres and 12 g of polylactic acid microfibers were mixed, and the weight ratio of polylactic acid nanospheres to polylactic acid microfibers was 1:4, to obtain polylactic acid fiber DB1.

[0259] Comparative Example DB-2

[0260] Polylactic acid fiber was prepared according to Example B-1, except that 12 g of polylactic acid nanospheres and 3 g of polylactic acid microfibers were mixed, and the weight ratio of polylactic acid nanospheres to polylactic acid microfibers was 4:1, to obtain polylactic acid fiber DB2.

[0261] Comparative Example DB-3

[0262] Polylactic acid fiber was prepared according to Example B-1, except that in the preparation of (1) polylactic acid nanospheres, ultrasound was applied at 25°C and 1000W for 30 minutes to obtain polylactic acid fiber DB3.

[0263] Preparation of copolymer fiber compositions

[0264] The formulas of copolymer fiber compositions C1-C10 and DC1-DC7 are shown in Table 1

[0265] Table 1

[0266]

[0267]

[0268] At 30°C and a pipe column diameter of 10 mm, the changes in indoor drag reduction rates of copolymer fiber compositions C1-C10 and DC1-DC7 with different contents (0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%) in clean water and 10wt% standard brine were studied. The standard brine was prepared in accordance with SY / T5107-2005 "Method for evaluating the performance of water-based fracturing fluids". Specifically, the standard brine composition is: 2.0wt% KCl + 5.5wt% NaCl + 0.45wt% MgCl2 + 0.55wt% CaCl2. The results are shown in Table 2.

[0269] Table 2

[0270]

[0271]

[0272]

[0273]

[0274]

[0275] It can be seen from the results in Table 2 that the indoor drag reduction rate of the copolymer fiber composition of Examples 1 to 10 of the present invention is maintained at above 70%, which has an excellent drag reduction rate.

[0276] Application Examples

[0277] Application Example 1

[0278] 1.5 parts by weight of the copolymer fiber composition C1, 0.1 parts by weight of potassium persulfate, and 100 parts by weight of water were mixed to obtain a fracturing fluid E1.

[0279] Application Example 2

[0280] 1 part by weight of the copolymer fiber composition C2, 0.3 parts by weight of sodium persulfate, and 100 parts by weight of water were mixed to obtain a fracturing fluid E2.

[0281] Application Example 3

[0282] 0.5 parts by weight of the copolymer fiber composition C2, 0.1 parts by weight of ammonium persulfate, and 100 parts by weight of water were mixed to obtain a fracturing fluid E3.

[0283] Application Example 4-10

[0284] The fracturing fluid was prepared according to Application Example 1, except that the copolymer fiber compositions were C4-C10, respectively, to obtain fracturing fluids E4-E10.

[0285] Application Comparative Examples 1-7

[0286] The fracturing fluid was prepared according to Application Example 1, except that the copolymer fiber compositions were DC1-DC7, respectively, to obtain fracturing fluids DE1-DE7.

[0287] Application Comparative Example 8

[0288] 2 parts by weight of the copolymer fiber composition C1, 0.6 parts by weight of potassium persulfate, and water were mixed to obtain fracturing fluid DE8.

[0289] Test Case

[0290] The performance parameters of fracturing fluids E1-E10 and DE1-DE8 are shown in Table 3. The appearance of the fluid was observed by standing the fracturing fluid at 25°C for 10 min.

[0291] Table 3

[0292]

[0293]

[0294] It can be seen from the results in Table 3 that the fracturing fluids prepared using the copolymers provided in Examples 1-10 of the present invention have excellent high temperature resistance, easy sand carrying and low friction properties.

[0295] Figure 1 This is a graph showing the heat resistance and shear resistance of the fracturing fluid prepared in Application Example 1. As can be seen from the graph, the fracturing fluid provided by the present invention can still maintain a high apparent viscosity at 158°C and has excellent high temperature resistance and shear resistance.

[0296] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A copolymer, characterized in that The copolymer contains a structural unit A represented by Formula 1, a structural unit B represented by Formula 2, a structural unit C represented by Formula 3 and / or Formula 4, and a structural unit D represented by Formula 5 and / or Formula 6. Wherein, in Formula 1, R1 is hydrogen or methyl; In formula 2, R2 is hydrogen or methyl; In formula 3, R3 is hydrogen or methyl; R4 is Wherein, R5 and R5' are each independently hydrogen, methyl or Where R 12 is a C2-C6 straight chain or branched chain alkylene; In formula 4, R6 is hydrogen or methyl; R7 is methyl, benzyl or Where R 13 is methylene, C2-C6 straight chain or branched alkylene; n is an integer of 1-4; In Formula 5, R8 is hydrogen or methyl; R9 is Among them, R 14 C 10 -C 20 A straight chain or branched alkyl group; In formula 6, R 10 is hydrogen or methyl, R 11 for Wherein, based on the total weight of the copolymer, the content of the structural unit A is 40-60wt%, the content of the structural unit B is 20-30wt%, the content of the structural unit C is 15-20wt%, and the content of the structural unit D is 5-25wt%.

2. The copolymer according to claim 1, wherein Based on the total weight of the copolymer, the content of structural unit A is 45-55wt%, the content of structural unit B is 20-25wt%, the content of structural unit C is 15-18wt%, and the content of structural unit D is 5-17wt%; Preferably, in Formula 1, R1 is hydrogen; Preferably, in Formula 2, R2 is hydrogen; Preferably, in Formula 3, R3 is hydrogen; R4 is R5 and R5' are each independently methyl or Where R 12 is a C2-C4 straight or branched alkylene group, more preferably, R5 and R5' are methyl groups, or, R5 is methyl group and R5' is Where R 12 for Preferably, in Formula 4, R6 is hydrogen or methyl; R7 is methyl or benzyl, and n is 2 or 3. More preferably, R6 is methyl, R7 is methyl, and n is 2 or 3. Preferably, in Formula 5, R8 is hydrogen; R9 is Among them, R 14 C 15 -C 20 A straight or branched alkyl group, more preferably, R 14 for Preferably, in Formula 6, R 10 For hydrogen.

3. The copolymer according to claim 1 or 2, wherein The weight average molecular weight of the copolymer is 8 million g / mol to 10 million g / mol, preferably 8.5 million g / mol to 9 million g / mol.

4. A method for preparing a copolymer, characterized in that: The preparation method comprises: (1) first mixing monomer 1, monomer 2, monomer 3 and water to obtain an aqueous solution; wherein the monomer 1 has a structure shown in formula I, the monomer 2 has a structure shown in formula II, and the monomer 3 has a structure shown in formula III and / or formula IV; (2) in the presence of a first solvent, performing a second mixing of monomer 4 and an emulsifier to obtain an oil phase solution; wherein the monomer 4 has a structure represented by formula V and / or formula VI; (3) in the presence of a protective atmosphere and an initiator, the aqueous phase solution and the oil phase solution are subjected to a third mixing and polymerization to obtain the copolymer; Wherein, in formula I, R1 is hydrogen or methyl; In formula II, R2 is hydrogen or methyl; In formula III, R3 is hydrogen or methyl; R4 is Wherein, R5 and R5' are each independently hydrogen, methyl or Where R 12 is a C2-C6 straight chain or branched chain alkylene; In formula IV, R6 is hydrogen or methyl; R7 is methyl, benzyl or Where R 13 is a C1-C6 straight chain or branched alkylene group; n is an integer of 1-4; In formula V, R8 is hydrogen or methyl; R9 is Among them, R 14 C 10 -C 20 A straight chain or branched alkyl group; In Formula VI, R 10 is hydrogen or methyl, R 11 for Wherein, based on the total mass of monomer 1, monomer 2, monomer 3 and monomer 4, the content of monomer 1 is 40-60wt%, the content of monomer 2 is 20-30wt%, the content of monomer 3 is 15-20wt%, and the content of monomer 4 is 5-25wt%.

5. The preparation method according to claim 4, wherein: The first mixing condition in step (1) includes: adjusting the pH to 6-7, the temperature to 20-30° C., and the time to 0.5-2 h; Preferably, the second mixing conditions in step (2) include: a stirring rate of 1000-1500 r / min, a stirring temperature of 20-30° C., and a stirring time of 10-30 min; Preferably, the third mixing condition in step (3) includes: a stirring rate of 1000-1600 r / min, a stirring temperature of 20-30° C., and a stirring time of 5-30 min; Preferably, the polymerization reaction conditions in step (3) include: temperature of 36-45° C., time of 2-3 h; Preferably, the polymerization in step (3) further comprises: adding a second solvent or an initiator so that the polymerization reaction temperature is 36-45° C.; Preferably, the concentration of monomer 1 in the aqueous phase solution is 30-40 wt %; Preferably, based on the total mass of the monomers, the emulsifier and the initiator, the content of the monomer 1, the monomer 2, the monomer 3 and the monomer 4 is 90-98.2wt%, the content of the initiator is 0.2-1.2wt%, and the content of the emulsifier is 1.6-9wt%; Preferably, the initiator is selected from at least one of an azo initiator, a peroxide initiator and a redox initiator, preferably selected from at least one of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, tert-butyl hydroperoxide, sodium sulfite and sodium bisulfite; Preferably, the first solvent is selected from at least one of kerosene, diesel, white oil, cyclohexane, benzene, toluene and petroleum ether; Preferably, the emulsifier is a nonionic surfactant, preferably at least one selected from sorbitan monostearate, sorbitan oleate, polyoxyethylene sorbitan monostearate, polysorbate 80 and dodecylphenol polyoxyethylene ether; Preferably, the second solvent is water.

6. A copolymer obtained by the preparation method according to claim 4 or 5.

7. A polylactic acid fiber, characterized in that: The polylactic acid fibers include polylactic acid nanospheres and polylactic acid micron fibers; Wherein, the weight ratio of the polylactic acid nanospheres to the polylactic acid microfibers is 1:0.3-3; Wherein, the average particle size of the polylactic acid nanospheres is 122-143nm; Wherein, the average length of the polylactic acid micron fiber is 700-800 μm, and the average diameter is 600-800 nm.

8. A method for preparing polylactic acid fiber according to claim 7, characterized in that: The preparation method of the polylactic acid nanospheres comprises: (1) dissolving polylactic acid in an organic solvent 1 under ultrasonic conditions to obtain an organic phase 1; (2) adding the organic phase 1 of step (1) into water and mixing to obtain the polylactic acid nanospheres; The ultrasonic conditions in step (1) include: ultrasonic time of 10-30 min, ultrasonic power of 500-900 W, and temperature of 20-30° C. Preferably, the mixing conditions in step (2) include: a stirring speed of 500-700 r / min, a stirring temperature of 20-30° C., and a time of 10-30 min; Preferably, the organic solvent 1 is a mixed solution of ethanol and acetone; Preferably, the content of the L-isomer of the polylactic acid is 90-99 wt %.

9. A copolymer fiber composition, characterized in that The copolymer fiber composition comprises the copolymer according to any one of claims 1 to 3 and 6, the polylactic acid fiber according to claim 7 or the polylactic acid fiber prepared by the preparation method according to claim 8, a surfactant and an inhibitor; Wherein, the copolymer fiber composition comprises: 85-95 parts by weight of the copolymer; 0.5-1.5 parts by weight of the polylactic acid fiber; 5-10 parts by weight of the surfactant; The polymerization inhibitor is 0.05-0.1 parts by weight; Preferably, the surfactant is selected from at least one of nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether and dodecylphenol polyoxyethylene ether; Preferably, the polymerization inhibitor is selected from at least one of polyvinyl alcohol, sodium polyacrylate and sodium alginate.

10. A fracturing fluid, characterized in that: The fracturing fluid comprises the copolymer fiber composition of claim 9, a breaker and water; Wherein, the fracturing fluid comprises: 0.5-1.5 parts by weight of the copolymer fiber composition; The debonding agent is 0.1-0.5 parts by weight.

11. Use of the fracturing fluid according to claim 10 in reservoir exploration and development.

Citation Information

Patent Citations

  • High-strength fiber fracturing fluid and preparation method and application thereof

    CN108841370A

  • Reinforcing agent of amphoteric polyacrylamide cardboard paper

    CN101666059A

  • Emulsion encapsulating and inhibiting agent for drilling liquid, and production technology and application of emulsion encapsulating and inhibiting agent

    CN106349426A

  • Ink jet recording medium

    US5439739A